Pendekatan sistem untuk memahami jalur emisi carbon dan manfaat ekonomi pada rantai pasokan di umkm tempeh jawa barat - Fadil Abdullah; Hafizah Aprilia; Siti Nur Hamidah (Airlangga Journal of Innovation Management, 2025)
This study aims to identify and map the tempeh industry's supply chain to understand the economic pathway and carbon emissions. The research method uses a system-based approach with the output of a causal loop diagram that explores the dynamic relationship between variables in the small and medium scale tempeh industry supply chain. The results showed that the potential of the small and medium-scale tempeh industry in West Java is very high, especially in contributing to the economic value of the surrounding community. However, this potential has challenges regarding raw material procurement, where dependence on imported soybean raw material supplies makes the economic value for MSEs or the surrounding community not too large. This is due to the efficiency in the procurement of local soybeans and the inadequate stock of local soybean resilience to meet the needs of tempeh production in West Java’s supply chain. The findings also show that the longer the supply chain, the smaller the profitability and create more environmental impacts related to the carbon emissions generated. This study recommends a policy meeting to cut and streamline, and prioritize local soybeans and increase local soybean resilience stocks to better benefit tempeh SMEs in gaining profitability and minimizing the impact of carbon footprint risks, so that business and industrial activities are more sustainable.